Amphetamine-induced alteration to gaze parameters: A novel conceptual pathway and implications for naturalistic behavior. (April 2021) - Hayley, Amie C.; Shiferaw, Brook; Downey, Luke A.
Highlights: We propose a novel model for amphetamine-induced alterations to gaze behavior. Gaze parameters are dependent on visual input via component oculomotor processes. Amphetamine reduces continuity and accuracy of visuomotor movement and control. Mismatch between these systems produces perceptual narrowing or 'tunnel vision'. Quantifying gaze behaviour may index amphetamine-related visual scanning efficiency. Abstract: Amphetamine produces a multiplicity of well-documented end-order biochemical, pharmacological and biobehavioural effects. Mechanistically, amphetamine downregulates presynaptic and postsynaptic striatal monoamine (primarily dopaminergic) systems, producing alterations to key brain regions which manifest as stereotyped ridged behaviour which occurs under both acute and chronic dosing schedules and persists beyond detoxification. Despite evidence of amphetamine-induced visual attentional dysfunction, no conceptual synthesis has yet captured how characteristic pharmaco-behavioural processes are critically implicated via these pathways, nor described the potential implications for safety-sensitive behaviours. Drawing on known pathomechanisms, we propose a cross-disciplinary, novel conceptual functional system framework for delineating the biobehavioural consequences of amphetamine use on visual attentional capacity and discuss the implications for functional and behavioural outcomes. Specifically, we highlight the manifest implications for behaviours that are conceptually driven and highly dependent on visual information processing for timely execution of visually-guided movements. Following this, we highlight the potential impact on safety-sensitive, but common behaviours, such as driving a motor vehicle. The close pathophysiological relationship between oculomotor control and higher-order cognitive processes further suggests that dynamic measurement of movement related to the motion of the eye (gaze behaviour) may be a simple, effective and direct measure of behavioural performance capabilities in naturalistic settings. Consequently, we discuss the potential efficacy of ocular monitoring for the detection and monitoring of driver states for this drug user group, and potential wider application. Significance statement: We propose a novel biochemical-physiological-behavioural pathway which delineates how amphetamine use critically alters oculomotor function, visual-attentional performance and information processing capabilities. Given the manifest implications for behaviours that are conceptually driven and highly dependent on these processes, we recommend oculography as a novel means of detecting and monitoring gaze behaviours during naturalistic tasks such as driving. Real-word examination of gaze behaviour therefore present as an effective means to detect driver impairment and prevent performance degradation due to these drugs.